2016
DOI: 10.1021/acs.cgd.6b00945
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Flexibility and Halogen Bonding in Thyroid Hormones and Their Metabolites

Abstract: Iodothyronamines (TAMs) are endogenous thyroid hormone (TH) metabolites, which are proposed to be biosynthesized by decarboxylation of the β-alanine side chain of THs. Iodothyronine deiodinases (DIOs) mediate phenolic and tyrosyl ring deiodinations of thyroid hormones and play an important role in thyroid hormone homeostasis. These enzymes also accept iodothyronamines as substrates for deiodination, but the binding affinities of TAMs to DIOs are lower than that of THs. In this paper, we report, for the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…A mechanism for T4 deiodination by naphthyl‐based deiodinase mimics was proposed involving the formation of halogen bonding (XB) between chalcogen and iodine atoms . Both experimental results and theoretical investigations demonstrated that the formation of a halogen bond between chalcogen and iodine atoms is crucial for the biomimetic deiodination to occur . Very recently, the Mugesh's group proved that the tellurol containing species, ( 4 and 5 in Scheme ), show a considerably increased deiodination rate .…”
Section: Introductionmentioning
confidence: 99%
“…A mechanism for T4 deiodination by naphthyl‐based deiodinase mimics was proposed involving the formation of halogen bonding (XB) between chalcogen and iodine atoms . Both experimental results and theoretical investigations demonstrated that the formation of a halogen bond between chalcogen and iodine atoms is crucial for the biomimetic deiodination to occur . Very recently, the Mugesh's group proved that the tellurol containing species, ( 4 and 5 in Scheme ), show a considerably increased deiodination rate .…”
Section: Introductionmentioning
confidence: 99%
“…However, the binding of THs to DIOs in different conformations is yet to be experimentally verified. [52,53]…”
Section: Metabolism Of Thyroid Hormonesmentioning
confidence: 99%